Perilaku Petani Dalam Manajemen Sumber Daya Pertanian Tanaman Pangan di Wilayah Muna Barat Provinsi Sulawesi Tenggara - Widayati, Weka (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2011)
The aim of the research was (1) to study the behavior of farmers in agricultural resources management (planning, actuating and evaluation of land, water, labor, and technology) (2) to study specification of the behavior of farmers in agricultural resources management in region west Muna. Method of research was used survey. Research area is divided into two-dimensional spatial which are the area between the average lowest ebb-arbitrary from the tidal line (region I) and the territory between the arbitrary line of tidal form land borders (region II). The population is farmers with at least four seasons farming crops in the West Muna with proportional random sampling. Data collection techniques were observation and structured interviews. Data were analyzed with quantitative (descriptive statistical and test-t. The results of research of farmer’s behavior near the coastline(region I) has low behavior in crop resource management that includes: planning, actuating and evaluation of resources (water, field, labor, and technology), in contrary with crop farmers that are located far from the coastline in West Muna. Each region has combinations between farmer’s behavior in crop resource management that is oriented towards productivity and crop farming sustainability. The difference is due to the strength of local wisdom in the management of agricultural resources that underlie the behavior of farmers in region II. The behavior of farmers in resource management which refers to the orientation of agricultural productivity and sustainability of resources.